Gambaran Fungsi Eksekutif Pada Anak Kelas 1 Di SDN Kuin Utara 4 Banjarmasin - Wella Ananda; Ghea Amalia Arpandy; Aziza Fitriah (LPPM Universitas Proklamasi 45, 2024)
Executive function is a ability to adapt, to make initiation, to organize, and to process information and behaviour. Children who have good executive function abilities will have more learning potential. They can easily get along with peers and teachers at school, and can make one's quality of self improve. This study aims to look at the executive function in grade 1 primary school of SDN Kuin Utara 4 Banjarmasin. This research uses qualitative research with a case study approach. The subject retrieval technique used purposive sampling technique, which was selected with certain considerations, namely as many as 2 subjects. The data collection techniques used were interviews, observation, and documentation. The data analysis technique used is the Miles and Huberman model. The results showed that executive function in both subjects at SDN Kuin Utara 4 Banjarmasin had not developed according to age Keywords: Executive Function, Elementary School Children